Peningkatan Aktifitas dan Hasil Belajar Matematika melalui Metode Teams Games Tournament (PTK Pada Siswa Kelas VIIB SMP N 2 Sawit Tahun Ajaran 2014/2015) - Dwiyanto, Agus (2016)
The purpose of this research is to increase the activity and results of learning mathematics through games method tournament teams at VIIB grade students of SMP Negeri 2 Sawit academic year 2014/2015. Students as recipients numbered 30 Students. The study was conducted using research methods class action consisting of two cycles, with the first cycle and the second cycle, each consisting of two meetings. Data collection methods used in this study include observation, field notes, and documentation. Data analysis techniques performed by the flow method, which is a process of data analysis, data presentation, and data verification. The results showed an increase in activity and mathematics learning outcomes that can be seen from the following indicators: (1) Asking questions when learning takes place 21 students (70%), (2) Working on the questions in front of a class with 22 students (73.33%) , (3) Answering questions from the teacher with 24 students (80%), (4) students who graduated KKM many as 25 students (83.33%) The results of the above description is concluded that the application of learning methods Tournament Teams Games can improve the activity and learning outcomes VIIB math on grade students of SMP Negeri 2 Sawit academic year 2014/2015.